The Role of MSMEs and the Challenges of Their Development: A Qualitative Study Through MSME Owner Interviews - Muhammad Aqshel Revinzky Nizar; Rizky Ramadhan; Mochammad Chairul Ihsan; Cattleya Rejito; Rd. Rifqi Dwisanto; Adhadian Akbar (CV Putra Publisher, 2026)
This community service program aims to strengthen the capacity and competitiveness of small businesses (UMKM) in Kecamatan Cibeunying, Bandung, through mentoring and business assistance. Background observations indicate that many UMKM still face limitations in marketing, financial management, and digital utilization, which hinder business growth and sustainability. The activity employed a participatory approach by conducting interviews and direct mentoring with selected UMKM actors to identify their main problems and needs. Assistance focused on improving basic financial recording skills, simple digital marketing (use of social media and online catalogs), and product packaging improvement. The results show an increase in participants’ understanding of financial management, better product presentation, and initial adoption of digital platforms for promotion. This program concludes that targeted, field-based mentoring can effectively improve the managerial and marketing capabilities of UMKM, and recommends periodic follow-up to ensure business continuity and development.